Chemical Characteristics and Evolutionary Patterns of Groundwater in the Daqing River Plain Area of Haihe Basin - MENG Ruifang; YANG Huifeng; BAI Hua; XU Buyun (Yankuang ceshi, 2023)
BACKGROUND Groundwater is closely related to surface water. Groundwater over-extraction has triggered a series of negative ecological effects in the Daqing River basin. The evolution of groundwater chemical characteristics is influenced by both natural and anthropogenic factors. The analysis of groundwater chemical characteristics can indicate the meteorological-hydrological and water-rock interaction during groundwater runoff, thus reflecting the groundwater circulation path, groundwater system characteristics and evolution laws, etc. It also helps to monitor groundwater dynamics and prevent the occurrence of groundwater pollution. OBJECTIVES To clarify the chemical characteristics and evolution of groundwater in the plain area of the Daqing River basin, which will be important for the rational development and utilization of water resources in the basin. METHODS 47 water samples from the shallow aquifer groups and 32 water samples from the deep aquifer groups were collected to analyze the main anions (Cl-, SO42-, NO3-) and cations (K+, Na+, Ca2+, Mg2+). The water chemistry characteristics and evolution laws were studied by using the water chemistry type, Gibbs model and ion ratio relationship. On-site portable water quality analyzer (HACH-HQ40d) was used to test pH (accuracy 0.01), total dissolved solids (TDS, accuracy 0.01) and other parameters, and groundwater samples were collected after the indicators were stabilized. All samples were sent to the laboratory at low temperature and stored in a refrigerator at 4℃, and groundwater alkalinity was determined by titration on the same day. Seven days later, the samples were sent to the Institute of Hydrogeology and Environmental Geology, Chinese Academy of Geological Sciences for testing of major anions (Cl-, SO42-, NO3-) and major cations (K+, Na+, Ca2+, Mg2+) using inductively coupled plasma-optical emission spectrometry (iCAP6300). The anion and cation charge balance error was less than 5%, and the anion and cation test accuracy was 0.01mg/L. RESULTS The test results showed that the largest deviation was in the water sample from Hanbao Village, Liu Lizhuang Town, Anxin County, Baoding City, Hebei Province, which was from the shallow aquifer groups, and the maximum TDS reached 6015.00mg/L. The TDS of the shallow aquifer groups ranged from 254.10 to 6015.00mg/L, with an average of 664.14mg/L, a large coefficient of variation and a large variation in TDS, indicating that the shallow aquifer groups were affected by meteorological and human factors. The TDS of the deep aquifer groups ranged from 197.10 to 691.40mg/L, with an average of 278.58mg/L, and the coefficient of variation was small, indicating that the groundwater of the deep aquifer groups was less affected by meteorological and human activities than that of the shallow aquifer groups. A small portion of the sampling points of the shallow aquifer groups in the area were brackish water and salt water. The TDS of the deep aquifer groups was generally less than 1000mg/L, which was suitable for use as a mining layer. The pH values of the shallow and deep aquifer groupss in the study area were not very different (7.35-8.92) and were alkaline. The NO3- maximum value of 298.40mg/L and SO42-maximum value of 3091.00mg/L in the shallow aquifer groups, but the average value was not significant, indicating that the shallow aquifer groups have caused nitrate and sulfate pollution in local areas due to agricultural activities and other effects.In the shallow layer of the study area, except for the difference in hydraulic conditions in the northern piedmont plain where flaky or spotty HCO3-Cl-SO4 and HCO3-Cl type water occurred, the anions in most of the piedmont plain were mainly HCO3 type, and the cations were mainly Ca and Ca-Mg and Mg-Ca. During the discharge of groundwater along the piedmont plain to the mouth of the alluvial fan, the cations changed from Ca-Mg type to Na type in order through Ca-Mg-Na, Na-Ca-Mg, Na-Mg-Ca, Na-Ca to Na type, and anions from HCO3 type to SO4 and Cl type via HCO3-SO4, HCO3-SO4-Cl, HCO3-Cl-SO4, SO4-Cl. The deep groundwater cations were relatively more complex, and the zonation was more obvious: from the piedmont plain to the bottom of the alluvial fan, the cations transition from Ca, Ca-Mg, Mg-Ca, Na-Mg-Ca (Mg-Ca-Na) type to Na-Ca and Na type water.The shallow aquifer groups were basically located in the area of water-rock interaction, and individual points showed some influence of evaporation concentration. The deep aquifer groups were subjected to water-rock interaction and less affected by evaporation and atmospheric precipitation. The analysis results showed that the milligram equivalent concentration ratio of (Ca2++Mg2+)+(HCO3-+SO42-) to Na++K+-Cl- was close to -1, indicating a more significant cation exchange effect. The groundwater samples in this study area were mostly distributed near the end elements of silicate minerals, indicating that weathering of silicate minerals (such as feldspar) was the main hydrogeochemical control factor in the study area, which was consistent with the lithological characteristics of aquifers in the groundwater of the Daqing River basin plain, and the test results also showed that HCO3- was the dominant ion in both shallow and deep aquifer groups.The SI values of calcite in the shallow aquifer groups in this study area ranged from -0.46 to 1.35, dolomite SI values from -0.88 to 3.02, gypsum SI values from -3.1 to -0.68, and rock salt SI values from -8.53 to -4.75, indicating that calcite and dolomite were partially saturated and partially unsaturated, and both gypsum and rock salt were unsaturated. Cl-/(Na++K+) could determine whether the groundwater was influenced by the dissolution of silicate rock. Most of the groundwater samples in this study area exhibited Cl-/(Na++K+) < 1, indicating that, in addition to rock salt in dissolved state, silicate mineral dissolution (e.g., potassium feldspar and sodium feldspar) was the main source of excess Na+ and K+. The Na+ content may also originate from cation exchange, and the high Cl-, the higher concentration may be the input of foreign contamination. The HCO3-/(Ca2++Mg2+) of the samples from the shallow aquifer groups was basically less than 1, showing excess Ca2+ and Mg2+, suggesting other sources of Ca2+ or Mg2+, while the (HCO3-+SO42-)/(Ca2++Mg2+) of the shallow aquifer groups was distributed above and below the 1∶1 line on both sides, suggesting that evaporite minerals (e.g. gypsum) may also be an important source of Ca2+ for the shallow aquifer groups, as evidenced by the unsaturated state of gypsum in groundwater, in addition to the increase in SO42- due to human activities. Both HCO3-/(Ca2++Mg2+) and (HCO3-+SO42-)/(Ca2++Mg2+) of the deep aquifer groups lay above the 1∶1 line, and the excess HCO3- implied silicate dissolution dominance, or the presence of cation exchange, leading to a lower Ca2+ content. (Cl-+SO42-)/(HCO3-) could indicate the dissolution status of evaporites and carbonates, and water samples from shallow and deep aquifer groups were mainly distributed in the (Cl-+SO42-)/(HCO3-)=1∶1 line below, which indicated that its chemical components were more dissolved by carbonate rocks.In the influence zone of the Caohe River in the northern part of Mancheng District, the water chemistry changed from HCO3-Ca-Mg water to Cl-HCO3-Ca-Na water; at the alluvial fan margin of Jiehe River in Shunping County and at the alluvial fan margin of Rejected Horse River in Zhuozhou City, the proportion of Na content in groundwater gradually exceeded that of Mg as the cation content second only to Ca, and the water chemistry changed from HCO3-Ca-Mg water to HCO3-Ca-Na-Mg type water. The groundwater in the central plain changed from Cl-HCO3-Ca-Na and HCO3-Cl-Ca-Na type water with island and strip distribution of SO4-HCO3-Na-Mg, SO4-HCO3-Na, SO4-Na-Mg and HCO3-Na-Mg type water to Cl-HCO3-Ca-Na, SO4-Cl-Na-Mg type water dominated and mingled with HCO3-Cl-Ca-Mg, Cl-SO4-Na-Mg, HCO3-Cl-SO4-Na, HCO3-SO4-Na, HCO3-SO4-Na, HCO3-SO4-Na-Mg, and Cl-SO4-Na-Mg type water.The average NO3- content of the shallow aquifer was 28.78mg/L, and the average NO3- content of the deep aquifer was 4.55mg/L, indicating that nitrate pollution was serious in the shallow groundwater local area of the study area. Referring to the groundwater quality standard (GB/T 14848—2017) for ClassⅢ water, there were 17 sampling points in the shallow aquifer groups with NO3- content over 20mg/L and 5 sampling points in the shallow aquifer groups with SO42- greater than 250g/L, indicating that these sampling sites were affected by anthropogenic activities, resulting in nitrate and sulfate pollution. A ratio of SO42-/Ca2+ to NO3-/Ca2+ greater than 1 indicated that industrial and mining activities had a greater impact on groundwater, and a ratio less than 1 was more disturbed by agricultural activities and residential sewage. The results showed that the ratio of the deep aquifer groups was greater than 1, and only the 240m well in the north of Erlangmiao Village, Dingzhou City, Baoding City, Hebei Province, was less than 1. This indicated that the deep aquifer groups were basically affected by industrial and mining activities, but not by agricultural activities and residential sewage. In the shallow aquifer groups, there were 27 water samples with SO42--Ca2+ to NO3-Ca2+ ratio greater than 1, and 20 water samples with SO42--Ca2+ to NO3--Ca2+ ratio less than 1, indicating that the shallow aquifer groups were partly influenced by industrial and mining activities, and partly influenced by agricultural activities and domestic sewage of residents. CONCLUSIONS The characteristics and evolution of groundwater chemistry in the plain area of the Daqing River basin was investigated by using the water chemistry method, clarifying the characteristics of the water chemistry and the evolution of water chemistry types in the plain area of the Daqing River Basin. Reasons for the evolution trend were also investigated, indicating that the evolution of groundwater chemistry is increasingly influenced by human activities. Relevant research will be conducted on the prediction of the future evolution of water chemistry.